Detection of multiple mycotoxin occurrences in soy animal feed by traditional mycological identification combined with molecular species identification. (2015) - Gutleb, A.C.; Caloni, F.; Giraud, F.; Cortinovis, C.; Pizzo, F.; Hoffmann, L.; Bohn, T.; Pasquali, M.
Highlights: A mycological and toxigenic screening was carried out on soy samples for feed use. Aspergillus spp. and Fusarium spp. were found to frequently colonize soy. Aflatoxin was the most common mycotoxin detected. No DON producers were isolated despite DON occurrence. Abstract: Soy products are a main component of animal feed. Because mycotoxins may harm farm animals, undermining productivity and health, a mycological and toxigenic screening was carried out on 36 batches used in animal feed, collected in 2008, 2009 and 2010 in Italy. The investigated mycoflora of a subset of soy seed ( n = 6) suggested that Aspergillus spp. and Fusarium spp. frequently colonize soy seeds. Aflatoxins, fumonisins and deoxynivalenol were detected in 88.9%, 72.2% and 30.6% of samples, respectively. Co-occurrence of at least two toxins was observed in 72% of cases. The molecular analysis of the Fusarium spp. population identified Fusarium verticillioides as potential producers of fumonisins, but no known deoxynivalenol producers were detected. It is suggested that the widespread presence of toxins can be due to non-optimal storing conditions of the feed. Moreover, our results suggest that mycotoxin thresholds should be adapted to consider the frequent case of toxin co-occurrence. This approach would better reflect the real toxigenic risk of feedstuffs.